2008
DOI: 10.1029/2007jf000757
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fabric of sheared till: A strain indicator for evaluating the bed deformation model of glacier flow

Abstract: [1] Wet-based portions of ice sheets may move primarily by shearing their till beds, resulting in high sediment fluxes and the development of subglacial landforms. This model of glacier movement, which requires high bed shear strains, can be tested using till microstructural characteristics that evolve during till deformation. Here we examine the development of magnetic fabric using a ring shear device to deform two Wisconsinage basal tills to shear strains as high as 70. Hysteresis experiments and the depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
87
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(98 citation statements)
references
References 78 publications
10
87
1
Order By: Relevance
“…A1). Hooyer et al (2008) observed this same behavior in ring-shear experiments on two other basal tills and provided an explanation based on the observation that the silt-sized magnetite grains that dominated AMS resided mostly in larger rock particles. Although these larger host particles rotate during shear, their long-axis orientations do not reflect orientations of the magnetic particles within them, which cannot align with strain.…”
Section: Till Fabrics Based On Amssupporting
confidence: 61%
See 1 more Smart Citation
“…A1). Hooyer et al (2008) observed this same behavior in ring-shear experiments on two other basal tills and provided an explanation based on the observation that the silt-sized magnetite grains that dominated AMS resided mostly in larger rock particles. Although these larger host particles rotate during shear, their long-axis orientations do not reflect orientations of the magnetic particles within them, which cannot align with strain.…”
Section: Till Fabrics Based On Amssupporting
confidence: 61%
“…4) for this till is very similar to that measured for two basal tills from ice lobes that were on either side of the Green Bay lobe (Superior and Lake Michigan lobes, Hooyer et al, 2008) during the late-Wisconsinan. For these two tills, silt-sized magnetite grains were independently determined to be largely responsible for their AMS , using hysteresis experiments and the dependence of susceptibility on temperature.…”
Section: Till Fabrics Based On Amssupporting
confidence: 53%
“…This lack of common understanding provides clear motivation for experimentally studying particle and magnetic fabric evolution as a function of shear-strain magnitude and orientation (Hooyer and Iverson, 2000b;Thomason and Iverson, 2006;Hooyer et al, 2008;Iverson et al, 2008;Shumway and Iverson, 2009). To date, experiments have been carried out with five different tills and a linear-viscous putty subjected to a state of strain in the ISU ring-shear device close to simple shear.…”
Section: Grain and Magnetic Fabric Development During Bed Shearmentioning
confidence: 97%
“…The direction of shearing is along the x axis, and the sense of shearing in the stereonets is bottom north and top south. Stereonet labels indicate experiment number and the number, n, of AMS samples (fromHooyer et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation